Penetration of Trichobilharzia cercariae into mammals: dangerous or negligible event? - Horák, Petr; Mikeš, Libor; Aldhoun, Jitka A; Kolářová, Libuše (Parasite, 2008)
Bird schistosomes and cases of human cercarial dermatitis occur worldwide, but the number of cases is not monitored. Experiments with two schistosomes, namely Trichobilharzia szidati and T. regenti, show that they possess potent tools to penetration bird and mammalian skin, as well as exhibit species-specific migration patterns within vertebrate bodies. Therefore, the infections may affect different organs/tissues e.g. lungs or spinal cord. In this minireview, the adaptations and pathogenic effects of bird schistosomes in experimental mammals are discussed, and some ideas/hypotheses on risks to humans from exposure to bird schistosome cercariae are expressed.
Keywords: druhová specificita; Animals; ptáci; parazitární onemocnění plic; Humans; Lung Diseases, Parasitic; Adaptation, Physiological; lidé; financování organizované; zvířata; fyziologická adaptace; Lymnaea; Financing, Organized; nemoci míchy; Spinal Cord Diseases; Birds; Trematode Infections; Schistosomatidae; infekce červy třídy Trematoda; Species Specificity